MAFLD in COVID-19 patients: an insidious enemy. (2nd October 2020) - Dongiovanni, Paola; Meroni, Marica; Longo, Miriam; Fracanzani, Anna Ludovica
ABSTRACT: The pandemic Sars-CoV-2 infection represents a dramatic health challenge worldwide. Pneumonia is considered the major damage caused by the virus. However, recent data have highlighted the impact of the Sars-CoV-2 related disease namely COVID-19 on the liver. Hepatic abnormalities significantly increase during COVID-19 and a more severe infection occurs in patients with pre-existing liver diseases, among which the most frequent is metabolic-associated fatty liver disease (MAFLD). It has been described that MAFLD patients had a higher risk of progression to severe COVID-19, higher abnormal liver tests and longer viral shedding time. The presence of fibrosis in MAFLD patients is another risk factor for severity of COVID-19. Due to the overgrowing prevalence of MAFLD, it could be speculated that a large proportion of the population might be at risk of severe COVID-19 and the identification of these patients possibly by using liver enzymes as risk predictors may be crucial for an early diagnosis and for the management of the infection.